2019
DOI: 10.4236/fns.2019.107061
|View full text |Cite
|
Sign up to set email alerts
|

Cottonseed Protein, Oil, and Mineral Nutrition in Near-Isogenic <i>Gossypium hirsutum</i> Cotton Lines Expressing Leaf Color Phenotypes under Field Conditions

Abstract: Information about the effects of phenotype traits on cottonseed protein, oil, and nutrients is scarce. The objective of this research was to investigate the effects of leaf color trait on seed nutrition in near-isogenic Gossypium hirsutum cotton expressing green (G) and yellow (Y) leaf color phenotypes. Our hypothesis was that leaf color can influence the accumulation of nutrients in seeds. Sets of isogenic lines were: DES 119 (G) and DES 119 (Y); DP 5690 (G) and DP 5690 (Y); MD 51ne (G) and MD 51ne (Y); SG 74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…For example, B showed: (1) its involvement in RNA through uracil; cell division and differentiation; seed maturation; respiration; pollen germination, growth, and stability; and seed quality [ 7 , 18 , 19 , 40 , 41 , 42 , 43 ]; (2) involvement of Cu in chloroplast protein plastocyanin; electron transport system linking photosystem I and II; participation in protein and carbohydrate metabolism; involvement in enzymes such as oxidases for cytochrome, ascorbic, and polyphenol; and involvement in the desaturation and hydroxylation of fatty acids (7,40); (3) involvement of Mn in the oxidation reduction processes in the photosynthetic electron transport system, essential for photosystem II for photolysis; acting as a bridge for ATP and enzymes for phosphokinase and phosphotransferases; and activating IAA oxidases (7,40); (4) the involvement of Ni in disease resistance; nickel enzymes, proteins urease, and glyoxylase; and protein metabolism [ 7 , 40 , 44 ]. Previous research showed that micro-nutrients responded to phenotype traits, and micro-nutrients’ levels in plant tissues resulted in yield and seed quality differences [ 7 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, B showed: (1) its involvement in RNA through uracil; cell division and differentiation; seed maturation; respiration; pollen germination, growth, and stability; and seed quality [ 7 , 18 , 19 , 40 , 41 , 42 , 43 ]; (2) involvement of Cu in chloroplast protein plastocyanin; electron transport system linking photosystem I and II; participation in protein and carbohydrate metabolism; involvement in enzymes such as oxidases for cytochrome, ascorbic, and polyphenol; and involvement in the desaturation and hydroxylation of fatty acids (7,40); (3) involvement of Mn in the oxidation reduction processes in the photosynthetic electron transport system, essential for photosystem II for photolysis; acting as a bridge for ATP and enzymes for phosphokinase and phosphotransferases; and activating IAA oxidases (7,40); (4) the involvement of Ni in disease resistance; nickel enzymes, proteins urease, and glyoxylase; and protein metabolism [ 7 , 40 , 44 ]. Previous research showed that micro-nutrients responded to phenotype traits, and micro-nutrients’ levels in plant tissues resulted in yield and seed quality differences [ 7 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…All the 13 elements we tested in cotton seeds are essential to plant growth (except for Na), animal nutrition, and human consumption (Bellaloui, Turley, Stetina, & Molin, 2019; Schroder, Zhang, Richards, & He, 2011). However, Cu, Mn, Ni, and Zn are also potentially toxic when their concentrations are too high.…”
Section: Discussionmentioning
confidence: 99%
“…In the examined eight parameters (P, Ca, K, Mg, Fe, Cu, Mn, and Ash) of cottonseed affected by fertilization management practices, He et al (2013b) Mn was correlated (p ≤ .05) positively with merely Fe, but negatively with Ca and Cu in their 2009 data, and not significantly correlated in any parameters in their 2010 data or combined 2-yr data. However, with near-isogenic cotton lines expressing different phenotypes, Bellaloui et al (2015aBellaloui et al ( , 2019 observed significant correlations of Mn with P as well as several other elements. The results of correlation analysis would be helpful to understand the observations of those parental and progeny lines co-appeared in top five maximal or minimal contents of more than one tested elements (Tables 1-5).…”
Section: Fementioning
confidence: 92%
“…Calibrations were developed using Perten’s Thermo Galactic Grams PLS IQ software, and the calibration equation was established according to AOAC methods AOAC, 1990a [ 60 ]; AOAC, 1990b [ 61 ]. Protein and oil were expressed on a seed dry matter basis [ 62 , 63 ]…”
Section: Methodsmentioning
confidence: 99%